RANCANG BANGUN SISTEM MONITORING KEAMANAN RUMAH BERBASIS WEB MENGGUNAKAN RASPBERRY PI B+ SEBAGAI SERVER DAN MEDIA KONTROL - Syabibi, Muhammad Khoiru; Subari, Arkhan (Gema Teknologi, 2016)
Muhammad Khoiru Syabibi, Arkhan Subari  in this paper explain that Along with the progress of era, the development of advanced technology also impacts on the development of security systems. Sophisticated security systems that digitally integrated has been growing, one of them is a web-based security system. This web-based home security monitoring system uses a raspberry pi b + that serves as a server and media controller, then for the web programming, it uses HTML, CSS and Javascript. This web-based home security monitoring system home uses a webcam (web camera) that functions like CCTV which can be monitored via a web browser, magnetic switch as security detector, keypad as access control to turn off security monitoring system for 10 seconds, and the buzzer and LED as security indicators. When someone enter the house, he/she must press the keypad. If keypad input is correct according to the passcode then the LED will turn off, indicate that home security monitoring system off for 10 seconds. If he/she enter the house without pressing the keypad according to the passcode then when the door opens, a switch magnetic will active, then buzzer will sound and the indicator on the web will change, indicate that he/she is a person who will do the crime.Keyword : raspberry pi b+, webcam, magnetic switch, keypad, buzzer and LED. ReferencesAndre. 2014. Sejarah PHP dan Perkembangan Versi PHP. http://www.duniailkom.com/sejarah-php-dan-perkembangan-versi-php.Apache Software Foundation. About the Apache HTTP Server Project. http://httpd.apache.org/ABOUT_APACHE.html.Arfa. 2014. Akses Kontrol Kendaraan Bermotor Roda Empat Menggunakan Password dan Sensor. Skripsi. Jakarta: STMIK Raharja.Aziz, Abdul. 2012. Pengertian, Fungsi, Serta Cara Kerja Web Server. http://www.dedeerik.com/pengertian-fungsi-serta-cara-kerja-web-server.Baharudin, M. 2011. Pengertian Website. http://www.naevaweb.com/pengertian-website/arsip.html.Cox, Tim. 2014. Raspberry Pi Cookbook. Birmingham: Packt Publishing.Embedded Linux Wiki. Raspberry Pi, Low-level Peripherals. http://elinux.org/RPi_Low- level_peripherals.Embededdlinux. Raspberry Mode B-Block diagram. Diunduh http://embeddelinux01.com.Faizal. 2011. Prinsip Kerja Piezoelectric. http://www.insinyoer.com/prinsip-kerja-piezoelectric.Friedl, Stave. 2015. Secure Linux/Unix Access With Putty and Open SSH. http://unixwiz.net/techtips/putty-openssh.html/2015.Gudang Linux. 2011. Python. http://gudanglinux.com/glossary/python.Gurevich, Vladimir. 2011. Electric Relays: Principles and Applications. London: CRC Press.Harian Android. 2014. Pengertian dan Fungsi SD Card. http://www.harianandroid.com/2014/04/pengertian-dan-fungsi-sd-card.html.Heranudin. 2011. Rancang Bangun Sistem Keamanan Ruangan Menggunakan Radio Frequency. Skripsi. Depok: FT UI.Iswan, Agusta. 2012. Sistem Proteksi Brankas Berpassword Menggunakan Magnetic Doorlock sebagai Penggerak Doorstrike Berbasis Mikrokontroller. Tugas Akhir D3 Teknik Elektro. Semarang: FT UNNES.Kho, Dickson. 2012. Dioda dan Fungsi Dioda. http://teknikelektronika.com/-dioda-fungsi-dioda.Kho, Dickson. 2012. Pengertian LED (Light Emitting Diode) dan Cara Kerjanya. http://teknikelektronika.com/pengertian-led-light-emitting-diode-cara-kerja.Kho, Dickson. Pengertian Resistor dan Jenis Resistor. http://teknikelektronika.com/pengertian-resistor-jenis-jenis-resistor.Komponen Elektronika. 2011. Rangkaian Buzzer. http://komponenelektronika.com/rangkaian- buzzer.html.MS-1 Magnetic Door Switch datasheet. http://www.braude.ac.il/files/departments/electrical_electronic_engineering/labs/data_pages/p3.pdfNasih, Muhammad Usman. 2013. Alat Pengaman Kendaraan Bermotor Menggunakan Password dan SMS. Tugas Akhir. Yogyakarta: STMIK El Rahma.Özcan, Yakut. 2014. Piezoelektrik.Paul Malvino, Albert. 2010. Prinsip-Prinsip Elektronika. Jakarta: Erlangga.Pemrograman Komputer. 2012. Petunjuk Praktikum Pemrograman Komputer. Semarang: D3 Teknik Elektro UNDIP.Prayitno, Indra. 2010. Kupas Tuntas Malwar. Jakarta: Elex Media Komputindo.Raspberry Pi Fondation. GPIO Raspberry Pi Model A dan B. https://www.raspberrypi.org/documentation/usage/gpio/2009Raspberry Pi Fondation. Setting Up And Apache Web Server On A Raspberry Pi. https://www.raspberrypi.org/documentation/remote-access/web-server/apache.md.Raspberrry Pi Fondation. SSH Using Windows. http://raspberrypi.org/documentation/remote-access/ssh/windows.md/2014Richardson, Matt dan Shawn Wallace. 2015. Make: Getting Started with Raspberry Pi. Sebastopol: Maker Media.Robinson, Andrew dan Mike Cook. 2014. Raspberry Pi Projects. Chichester: John Wiley & Sons Ltd.Rohiman, Ao. 2011. Pengertian dan cara kerja router.http://www.catatanteknisi.com/2011/05/pengertian-cara-kerja-router.html.Sidik, Betha. 2011. Javascript. Jakarta: Informatika.Wahyu. Pengertian Webcam dan Fungsinya. http://wahyu.blog.fisip.uns.ac.id/2011/12/06/pengertian-web-cam-dan-fungsinya.Wikipedia. Secure Digital. https://en.wikipedia.org/wiki/Secure_Digital#Micro.